Central vestibular dysfunction: don't forget vestibular rehabilitation. (3rd August 2022) - Zhang, Sulin; Liu, Dan; Tian, E.; Wang, Jun; Guo, Zhaoqi; Kong, Weijia
ABSTRACT: Introduction: Vestibular rehabilitation (VR) is now a subject of active studies and has been shown to be effective for multiple vestibular disorders, peripheral or central. VR is a physical therapy that helps train the central nervous system to compensate for vestibular dysfunction. There is moderate to strong evidence that VR is safe and effective for the management of peripheral vestibular dysfunction. Nonetheless, the studies on how VR works on central vestibular dysfunction remains scanty. Areas covered: This article addressed the rehabilitation strategies and possible mechanisms, including how central vestibular function might improve upon rehabilitation. In addition, it provides some examples concerning the effect of VR on central vestibular dysfunction. Expert opinion: VR works on the vestibular system through repetition of specific physical exercises that activate central neuroplastic mechanisms to achieve adaptive compensation of the impaired functions. VR has become a mainstay in the management of patients with dizziness and balance dysfunction. Individualized VR programs are a safe and effective treatment option for a large percentage of patients with central vestibular disease reporting imbalance and dizziness. Exploration of various treatment strategies and possible mechanisms will help develop the best and personalized VR treatment for patients with central vestibular dysfunction.